2013
DOI: 10.1002/jrs.4239
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of microcrystals in some ancient glass beads from china by means of confocal Raman microspectroscopy

Abstract: A total of ten ancient colored glass beads were analyzed by confocal Raman microspectroscopy for the non-destructive identification of microcrystals within them. These beads were excavated from different regions of China, including Xinjiang, Henan, Hubei and Guangxi Provinces, and were dated mainly from the 10 th century BC to the 9 th century AD. For the first time, either tin or antimony-based opacifiers/colorants including calcium antimonate (CaSb 2 O 6 , Ca 2 Sb 2 O 7 ), bindheimite (Pb 2 Sb 2 O 7 ), lead … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 27 publications
(33 reference statements)
3
33
0
Order By: Relevance
“…We previously identified the use of antimony‐based opacifiers and colorants in plant‐ash type and natron type soda–lime silicate glass beads (1000–400 bc ), which are distributed in the north of the Changjiang River . Evidence from the Chinese glasses analyzed here support Tite's suggested chronology for the use of antimony as an opacifying agent in the Mediterranean region.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…We previously identified the use of antimony‐based opacifiers and colorants in plant‐ash type and natron type soda–lime silicate glass beads (1000–400 bc ), which are distributed in the north of the Changjiang River . Evidence from the Chinese glasses analyzed here support Tite's suggested chronology for the use of antimony as an opacifying agent in the Mediterranean region.…”
Section: Resultssupporting
confidence: 71%
“…The various samples selected for analysis have similar shapes and decorations to those found in the tomb of Marquis Yi of the Zeng State (~433 bc ) in the Hubei Province. Over the past 20 years, a limited number of glass samples, and mainly fragments, have been analyzed from the tomb of Marquis Yi, and little Raman data have been published . In 2014, we analyzed 46 intact representative samples from this tomb in situ in the Hubei Provincial Museum without any sample pretreatment.…”
Section: Introductionmentioning
confidence: 99%
“…S3, the aforementioned stripes are not visible under the microscope, so we cannot clearly state that these compositional differences are associated to the variable colour of the glass layer. The Raman spectra acquired were divided into four groups according to the presence or absence of crystalline phases as following: (1) group in which the bands are at 477 and 636 cm −1 , attributed to cassiterite (Fig. , spectrum b, and Fig.…”
Section: Resultsmentioning
confidence: 92%
“…Moreover, in the whitish glass, calcium antimonate Ca 2 Sb 2 O 7 was identified on the basis of the bands at 634 and 481 cm −1 (Fig. , spectrum a), which presents a similar intensity , , , . Elemental mapping performed by VP‐SEM‐EDS confirmed that the whitish glass was enriched in both Ca and Sb (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Zhao and coworkers characterized microcrystals in some ancient glass beads from China by means of confocal Raman microspectroscopy. The beads were excavated from different regions of China, including Xinjiang, Henan, Hubei, and Guangxi Provinces, and were dated mainly from the 10th century BC to the 9th century AD …”
Section: Introductionmentioning
confidence: 99%